Measuring Positive and Negative Occupational States (PNOSI): Structural Confirmation of a New Belgian Tool - Marie Barbier; Stéphanie Peters; Isabelle Hansez (Psychologica Belgica, 2010)
This article reports on the validation of the Positive and Negative Occupational States Inventory (PNOSI), a new tool for measuring positive and negative occupational states. Three goals were defined: testing the structural validity of the PNOSI, testing its stability, and testing its convergent and discriminant validity with engagement, burnout, commitment, and workaholism. Data were collected in seven different companies (more than 16,000 participants). The factorial validity of the PNOSI was demonstrated using covariance structure analyses. A two-factor model with a negative occupational state factor and a positive occupational state factor fitted the data better than an alternative one-factor model. The two corresponding scales demonstrated good internal consistency. The results confirmed that positive and negative occupational states are distinct constructs and should be measured with different items. Convergent and discriminant validity with related constructs, namely engagement, burnout, commitment, and workaholism, were also demonstrated. The conclusion is that the PNOSI has good psychometric properties.